2018
DOI: 10.1002/acm2.12411
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of megavoltage electronic portal images for markerless tumor tracking

Abstract: PurposeThe poor quality of megavoltage (MV) images from electronic portal imaging device (EPID) hinders visual verification of tumor targeting accuracy particularly during markerless tumor tracking. The aim of this study was to investigate the effect of a few representative image processing treatments on visual verification and detection capability of tumors under auto tracking.MethodsImages of QC‐3 quality phantom, a single patient's setup image, and cine images of two‐lung cancer patients were acquired. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Consistent with that study, ISS stage at relapse in our cohort also retained prognostic significance. However, we did not find an effect of PFS1 on PFS2, which may have been due to the different treatment compared to the ASCT patients in the cohort in Cheong et al [15]. Moreover, Cheong et al [15] did not incorporate LDH, which we consider an important adverse prognostic indicator.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Consistent with that study, ISS stage at relapse in our cohort also retained prognostic significance. However, we did not find an effect of PFS1 on PFS2, which may have been due to the different treatment compared to the ASCT patients in the cohort in Cheong et al [15]. Moreover, Cheong et al [15] did not incorporate LDH, which we consider an important adverse prognostic indicator.…”
Section: Discussioncontrasting
confidence: 59%
“…Cheong et al [15] reported that among 269 relapsed MM patients who received ASCT between 2000 and 2014 at UCH Hospital in London, PFS1 retained independent prognostic significance (HR 0.91 [0.87–0.96, p = 0.001]), as did ISS stage 2/3 at relapse (HR 3.70 [1.58–8.66, p = 0.003]). Consistent with that study, ISS stage at relapse in our cohort also retained prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…The DRrPortRegistration was used for the registration between DRR images and port films, the mean absolute average errors in the DRrPortRegistration are equal to 0.2 degrees, 0.75 mm in the X-direction, and 0.81 in the Y-direction 17 . Cheong 18 reported that the CLAHE algorithm is the best effective step for the quality enhancement on the MV EPID image in terms to tumor tracking after comparing the individual contribution of deblurring, contrast improvement (CLAHE) and denoising, the detection errors in the contrast improvement group are 2.9 mm in the Y direction and 2.7 mm in the X-direction. The DRrPortRegistration and CLAHE algorithms showed an inferior accuracy than the present registration.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our proposed and comparative algorithms implementation on AP and lateral pelvis portal images and related 3D representation of intensity have been shown in Figures 6 and 7. Here, the results show a great improvement of less noise amplification and less blurring compared with these methods specially for Cheong et al 21 and Koutsofios et al 23 The artifacts of noise amplification and blurring normally occur in over enhancement in contrast with standard AHE (see Figure 8).…”
Section: Experimental Implementationmentioning
confidence: 66%
“…Moreover, the intensity improvement of bone edges relative to the background intensity values results in enhanced contrast in the processed image. From less noise amplification and less blurriness, Figure 6 shows a great improvement of the proposed method in comparison with comparative methods, especially for Cheong et al 21 . and Koutsofios et al 23 .…”
Section: Discussionmentioning
confidence: 93%